EKSPLORASI FAKTOR YANG MEMPENGARUHI KEPUTUSAN PASANGAN UNTUK BERCERAI DAN DAMPAKNYA BAGI ANAK - Salsabila Afida Putri; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
Domestic life does not always run smoothly. Problems that occur in the household are certainly unavoidable, not infrequently this can even lead to divorce. This divorce is always based on several problem factors, such as economic factors, domestic violence, and poor communication. The occurrence of parental divorce not only has an impact on the two divorced couples, but this will also have a major impact on the child. The purpose of this research is to find out the factors that influence married couples to divorce and what impact it has on children. The research method used is qualitative using library research techniques. Researchers obtain data starting with searching for literature studies from various literature sources such as articles, scientific journals, textbooks, or similar research results that have been published previously. The results showed that parental divorce can also affect children's emotions, children will experience stress and experience behavioral problems. Conversely, children who can accept their parents' divorce will be able to manage their emotions well.